ChemInform Abstract: Elucidation of Mechanisms and Selectivities of Metal‐Catalyzed Reactions Using Quantum Chemical Methodology. Issue 28 (June 2016) - Santoro, Stefano; Kalek, Marcin; Huang, Genping; Himo, Fahmi
Abstract: Review: 46 refs.